2013
DOI: 10.1186/1756-3305-6-187
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal variation in the prevalence of Anaplasma phagocytophilum and Borrelia burgdorferi sensu lato in questing Ixodes ricinus ticks in Norway

Abstract: BackgroundUnderstanding the variation in prevalence of Borrelia burgdorferi sensu lato (Lyme Borreliosis Spirochaetes, LBS) and Anaplasma phagocytophilum (causing tick-borne fever in ruminants and human granulocytic ehrlichiosis) in ticks is vital from both a human and an animal disease perspective to target the most effective mitigation measures. From the host competence hypothesis, we predicted that prevalence of LBS would decrease with red deer density, while prevalence of A. phagocytophilum would increase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 82 publications
8
35
0
Order By: Relevance
“…We detected lower prevalence of Borrelia infection in questing ticks from western regions with high density of red deer compared to the southeast, that could be due dilution of Borrelia in feeding ticks. Another study recently conducted in the west of Norway (Mysterud et al, 2013) confirmed the hypothesis of the dilution of B. burgdorferi s.l. in ticks in areas with high density of red deer.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…We detected lower prevalence of Borrelia infection in questing ticks from western regions with high density of red deer compared to the southeast, that could be due dilution of Borrelia in feeding ticks. Another study recently conducted in the west of Norway (Mysterud et al, 2013) confirmed the hypothesis of the dilution of B. burgdorferi s.l. in ticks in areas with high density of red deer.…”
Section: Discussionsupporting
confidence: 52%
“…We detected a significantly higher prevalence of Borrelia in adult ticks compared with nymphs and a higher infection rate among females than males (Table 2). Such differences were also registered in the study of Mysterud et al (2013) conducted along the western coast of Norway in 2011.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A. phagocytophilum was detected in 8.8% of I. ricinus in Sogn and Fjordane in a survey performed in 2011 [16], while an earlier study performed in 2006-7 found a lower prevalence (1.4% and 0.0% in two different locations, respectively) [17].…”
Section: Introductionmentioning
confidence: 97%
“…This is in line with previous studies in Europe that found a dilution effect of deer abundance on NIP for Borrelia burgdorferi s.l. 259,262,263 . In contrast, NIP for the two B. burgdorferi s.l.…”
Section: No Support For a Dilution Effect Of Host Species Richness | 133mentioning
confidence: 99%